Birth weight and its association with blood pressure and nutritional status in adolescents - Vanessa Roriz Ferreira; Thiago Veiga Jardim; Thais Rolim Póvoa; Karla Lorena Mendonça; Flávia Noggueira Nascente; Carolina Sousa Carneiro; Weimar Sebba Barroso; Polyana Morais; Maria Gondim Peixoto; Ana Luiza Lima Sousa; Paulo Cesar Brandão Veiga Jardim (Brazilian Society of Pediatrics, 2018)
Objective: The management of children with low birth weight is not the same in countries with different resources. The authors assessed the association of birth weight with blood pressure and nutritional status in a representative sample of adolescents from a Brazilian state, aiming to identify possible consequences of these differences. Methods: A cross-sectional school-based study was conducted with adolescents (12-18 years) enrolled in public and private schools. Birth weight, office blood pressure, home blood pressure measurements, and nutritional status (body mass index, height z-score for the age, and waist circumference) were assessed. The association of birth weight with the outcomes (blood pressure, height, body mass index, and waist circumference) was studied through univariate and multivariable linear regression models. Results: A total of 829 adolescents with a mean age of 14.6 ± 1.62 years were included; 43.3% were male, and 37.0% from private schools. The prevalence of low birth weight was 8.7%. Mild low height prevalence was higher among those adolescents with low/insufficient birthweight when compared to those with normal/high birth weight (11.7 vs. 4.2%; p < 0.001). In the multiple linear regression analysis, for each increase of 100 g in birth weight, height increased by 0.28 cm (95% CI: 0.18-0.37; p < 0.01). Birth weight did not influence office blood pressure and home blood pressure, body mass index, or waist circumference of adolescents. Conclusions: Birth weight was directly associated to height, but not associated to blood pressure, body mass index, and waist circumference in adolescents from an urban area of a developing country.